Structure and composition of the stream ichthyofauna of four tributary rivers of the upper Rio Paraná basin, Brazil - Castro, Ricardo M. C.; Casatti, Lilian [UNESP]; Santos, Hertz F.; Vari, Richard P.; Melo, Alex L. A.; Martins, Luiz S. F.; Abreu, Tatiana X.; Benine, Ricardo C.; Gibran, Fernando Z.; Ribeiro, Alexandre C.; Bockmann, Flávio A.; Carvalho, Murilo; et al. (My University, 2005)
The ichthyofauna of 24 stretches of streams, all of 100 m length and of fifth or lower order and most of second and third order, were sampled along four left bank tributaries (Rio do Peixe, Rio Aguapeí, Rio São José dos Dourados, lower Rio Tietê) of the main channel of the Rio Paraná in the state of São Paulo, southeastern Brazil. Sampling of the fish fauna at each of the six sites in the four basins incorporated a standardized fish collecting methodology and a standardized documentation of environmental data serving as the basis for a comparative analysis of the collecting locations. The 8,189 fish specimens collected represented six orders, 18 families, 42 genera, and 56 species, with a total biomass of 28.8 kg. Approximately 52% of the collected species were characiforms, 28% siluriforms, 9% gymnotiforms, 5% cyprinodontiforms, 4% perciforms, and 2% synbranchiforms. The most abundant of the species were the characiforms Astyanax altiparanae (15% of total) and Knodus moenkhausii (12% of total). The two species with the largest overall biomasses were A. altiparanae (34% of total biomass) and the siluriform Hypostomus sp. (8% of total biomass). Analysis of the trophic structure of the studied ichthyofauna indicated that the 10 numerically dominant species across the 24 sampled streams can be grouped into five guilds that are in decreasing order of numerical importance: omnivores, insectivores, insectivores/invertivores, periphytivores, and algivores. Species richness in the sampled stream stretches varied from six to 20 species with an average richness of 14. The species richness estimated by extrapolation for all 24 sampled stream stretches was 67 species. The Characidae are predominant among the collected specimens with approximately 50% of both individuals and biomass, a fact hypothesized to be a function of several attributes typical of the family. Six of the 56 collected species were new to science and six other species are of indefinite taxonomic status and require further analysis in order to determine their identity. © 2005 by Verlag Dr. Friedrich Pfeil.